2020
DOI: 10.1186/s12938-020-00768-1
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of finger tendon and synovial sheath in ultrasound image using deep convolutional neural network

Abstract: Background: Trigger finger is a common hand disease, which is caused by a mismatch in diameter between the tendon and the pulley. Ultrasound images are typically used to diagnose this disease, which are also used to guide surgical treatment. However, background noise and unclear tissue boundaries in the images increase the difficulty of the process. To overcome these problems, a computer-aided tool for the identification of finger tissue is needed. Results: Two datasets were used for evaluation: one comprised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Kuok et al developed a computer-aided soft tissue segmentation method using a deep convolutional neural network , to help distinguish tendon tissue from synovial sheath tissue in ultrasound images. The authors suggested the potential use of the method in diagnosis and ultrasound-guide treatment of trigger finger [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Kuok et al developed a computer-aided soft tissue segmentation method using a deep convolutional neural network , to help distinguish tendon tissue from synovial sheath tissue in ultrasound images. The authors suggested the potential use of the method in diagnosis and ultrasound-guide treatment of trigger finger [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are multiple clinical settings in which application of ML models can aid MSUS. These include the assessment of synovial tissue (15,18), tendon (19,20), cartilage (21) and nerve identification (11,22,23). When examining these structures, a ML algorithm can perform either recognition or a diagnostic task.…”
Section: Ai-based Techniques For Ultrasound Imagingmentioning
confidence: 99%